2009
DOI: 10.1017/s0029665109001347
|View full text |Cite
|
Sign up to set email alerts
|

Symposium 1: Joint BAPEN and British Society of Gastroenterology Symposium on ‘Coeliac disease: basics and controversies’ Dietitians are better than clinicians in following up coeliac disease

Abstract: It seems obvious to healthcare professionals that patients with coeliac disease should receive regular follow-up. Surprisingly, there is little evidence that patients benefit in terms of reduced morbidity or mortality. However, several authoritative bodies have published guidelines on the management of coeliac disease that recommend regular follow-up. There is good evidence that compliance with a gluten-free diet reduces the risk of complications such as osteoporosis or small bowel lymphoma. Compliance is enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Lack of adherence to the GFD has shown that this treatment is clearly a challenge for sufferers and requires significant adjustment for them and their families. Studies have shown that consistent follow-up, support and encouragement from dietitians and doctors are necessary for the well-being of patients with CD (8,17). We believe that our clinic represents a novel and effective means to provide this support.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Lack of adherence to the GFD has shown that this treatment is clearly a challenge for sufferers and requires significant adjustment for them and their families. Studies have shown that consistent follow-up, support and encouragement from dietitians and doctors are necessary for the well-being of patients with CD (8,17). We believe that our clinic represents a novel and effective means to provide this support.…”
Section: Discussionmentioning
confidence: 91%
“…A GFD can be demanding and expensive; the dietitian can ensure that patients achieve their nutritional goals and give them the knowledge to add variety to their meals. Along with their knowledge of nutrition, dietitians are practiced in motivational interviewing, providing the encouragement needed for a patient to make a lifestyle change (17). The educational package given to the patients and families in our clinic includes a general guide to CD and nutritional handouts (18)(19)(20) regarding a GFD.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that in our local community either physicians, patients, or both do not always want a biopsy to confirm CD. These children do not receive appropriate diagnostic confirmation and are also missing out on the support and education our clinic provides [ 4 , 23 , 24 ]. Hence, we undertook to pilot a SD approach in our clinic.…”
Section: Discussionmentioning
confidence: 99%
“…, 2009; Roma et al. , 2010), which is particularly important because gluten re‐exposure results in villous damage and an increased risk of osteoporosis and malignancy (Stuckey et al. , 2009).…”
Section: Introductionmentioning
confidence: 99%